Pollen Resources for the Honey Bee, Apis mellifera in Roi-Et Province, Thailand - Nanork Sopaladawan, Piyamas (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this research was to investigated pollen resources for the honey bee, Apis mellifera based on pollen morphology analysis. The samples of bee pollen loads and pollen of flowering plants were collected during September – November 2014 in Pathumrat district, Roi-Et province. Acetolysis technique was used for pollen preparation. Pollen morphology analysis was investigated under light microscope (LM). The results showed 22 species of blooming flowers and 14 plant species found in bee pollen loads. There were 8 plant families found among 14 plant species from bee pollen loads, including (1) Arecaceae (2) Asteraceae (3) Bignoniaceae (4) Caricaceae (5) Fabaceae (6) Iridaceae (7) Moringaceae and (8) Rubiaceae. Five plant species can be identified after compared to pollen morphology of blooming flowers, including (1) Carica papaya (2) Helianthus annuus (3) Ixora coccinea (4) Sesbania grandiflora (5) Sphagneticola trilobata and 9 unknown species. The information from this research will benefit both beekeepers and in crop pollination. There were 2 economic plant species (C. papaya and H. annuus) found in bee pollen loads, which indicated that A. mellifera could be a good pollinator for these crop pollination.